2018
DOI: 10.1175/jcli-d-17-0627.1
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Polar Amplification to Varying Insolation Conditions

Abstract: The mechanism of polar amplification in the absence of surface albedo feedback is investigated using an atmospheric model coupled to an aquaplanet slab ocean forced by a CO2 doubling. In particular, we examine the sensitivity of polar surface warming response under different insolation conditions from equinox (EQN) to annual mean (ANN) to seasonally varying (SEA). Varying insolation greatly affects the climatological static stability. The equinox condition, with the largest polar static stability, exhibits a b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 53 publications
2
28
0
Order By: Relevance
“…The aquaplanet experiments with annual‐mean insolation show qualitatively similar results (black lines in Figures S5b and S7, first column in Figure S8, and black x in Figure S9), except that the polar amplification is much reduced consistent with Kim et al. (2018).…”
Section: Results Of Locked Experimentssupporting
confidence: 81%
See 1 more Smart Citation
“…The aquaplanet experiments with annual‐mean insolation show qualitatively similar results (black lines in Figures S5b and S7, first column in Figure S8, and black x in Figure S9), except that the polar amplification is much reduced consistent with Kim et al. (2018).…”
Section: Results Of Locked Experimentssupporting
confidence: 81%
“…The cloud responses are different with annual‐mean insolation: The high‐latitude (poleward of 50°) low cloud is less prevalent, and its response to quadrupled CO 2 is much weaker (cf. Figure S10 with S6), due to the lack of inversion atop the high‐latitude boundary layer (Kim et al., 2018). The global mean net TOACRE response in the annual‐mean locked experiment is +1.6 W m −2 , corresponding to a global mean SST increases of +1.7 K without polar amplification (Figure S7a, blue line).…”
Section: Results Of Locked Experimentsmentioning
confidence: 99%
“…Origin of the nonlinearity How does the nonlinear cooling come about in the first place? Several sources of nonlinearity previously identified in climate system (asides from ocean dynamics) can give a cooling effect, to name a few: the nonlinear cooling effect of vertical masking of both clear-sky quantities (such as water vapor) and cloud 22 , the remnant effect of the stabilized small ice-cap instability giving rise to a greater cooling than a warming under opposite forcing perturbations 40 , the negative nonlinear cloud radiative effect at surface attached to the seasonality in the polar climate 41 , plus the nonlinear atmospheric dynamics 39,42 . An parallel investigation has been undertaken through a suite of methodically designed experiments wherein sea ice formation is disabled to form an ice-free climate (see Methods and ref.…”
Section: The Linear and Nonlinear Responsementioning
confidence: 99%
“…Snow cover is one of the main indicators of climate change and is mostly used in order to study the relationship between climate and cryosphere (Mudryk et al, ). In the last three decades, the polar and cold regions have experienced the most rapid warming on Earth, especially in the Northern Hemisphere (Kim et al, ). The quick increase of temperature in these regions is part of global warming, with regional amplifications due to the relationships established between land surface temperature, oceanic circulation, glacier fluctuations, snow cover extent and duration as well as atmospheric patterns (Juřicová and Fratianni (), Serreze and Barry (), Pithan and Mauritsen (), and Ballinger et al .…”
Section: Introductionmentioning
confidence: 99%
“…the most rapid warming on Earth, especially in the Northern Hemisphere (Kim et al, 2018). The quick increase of temperature in these regions is part of global warming, with regional amplifications due to the relationships established between land surface temperature, oceanic circulation, glacier fluctuations, snow cover extent and duration as well as atmospheric patterns (Juřicová and Fratianni (2018), Serreze and Barry (2011), Pithan and Mauritsen (2014), and Ballinger et al (2018) showed that Canada, such as many other northern and cold regions, experienced a rapid warming with a temperature increase of approximately 1.5 C over the 1950-2010 period and also a significant statistical decrease in the number of ice days in the 1974-2013 period .…”
mentioning
confidence: 99%